Attitude and subjective wellbeing of non-compliant mothers to childhood oral polio vaccine supplemental immunization in Northern Nigeria - Gregory C. Umeh; Terna Ignatius Nomhwange; Anthony F. Shamang; Furera Zakari; Audu I. Musa; Paul M. Dogo; Victor Gugong; Neyu Iliyasu (BMC Public Health, 2018)
Abstract Background Attitude and subjective well-being are important factors in mothers accepting or rejecting Oral Polio Vaccine (OPV) supplemental immunization. The purpose of the study was to determine the role of mothers’ attitude and subjective wellbeing on non-compliance to OPV supplemental immunization in Northern Nigeria. Methods The study utilized a cross-sectional design to assess attitude and subjective well-being of mothers using previously validated VACSATC (Vaccine Safety, Attitudes, Training and Communication-10 items) & SUBI (Subjective Well-being Inventory-40 items) measures. A total of 396 participants (equal number of non-compliant and compliant mothers) from 94 non-compliant settlements were interviewed, after informed consent. T-test was run to assess difference in mean scores between the non-compliant and compliant mothers on VACSATC and SUBI measures. Results The research showed a significant difference in mean scores between the non-compliant and compliant groups on VACSATC measure of mothers’ attitude (M = 18.9 non-compliant, compared to 26.5 compliant; p < 0.05). On subjective well-being, the study showed there was no significant difference in the mean scores of the SUBI measure (M = 77.4 non-compliant, compared to 78.0 compliant; p > 0.05). Conclusion The research has shown that negative attitude is more commonly present in non-compliant mothers and may be a factor in vaccine refusal in Northern Nigeria.